Low Noise Amplifier For Front End Transceiver At 5.8 GHz - M. H. Che Halim; Abd. Aziz, Mohamad Zoinol Abidin; Othman, Abdul Rani; Sahingan @ Samingan, Md Saiful Azri; M.F. Selamat; A.A. Abd Aziz (2008)
This paper presents the design of 5.8 GHz front end Low Noise Amplifier application for IEEE standard 802.11 systems for WLAN application. Revolution and demand of WLAN technology have urged development of low cost, low power and small size transceiver by using microstrip technology [1]. This paper is present design and simulation of single stage LNA circuits. This paper is focusing on development of Low Noise Amplifier operating at 5.75-5.85GHz (5GHz upper U-NII band) for WLAN application. The amplifier design used FHX76LP Low noise SuperHEMT from Eudyna Device USA Inc. The design circuit uses lumped elements to implement the matching networks. The purpose single stage of input and output matching network is to produces 50Ω impedance at the input and output port of the LNA. The matching network is used at both sides of the transistor [2],[3]. The target simulation are gain (S21)with >10dB, noise figure with <10dB and input and output return loss <-10dB at 5.8 GHz. A single stage LNA has successfully designed with 15.924 dB forward gain , 0.552 dB noise figure, -11.182 dB output return loss(S22) and -13.246 dB input return loss(S11) by using ADS software.